Volatile organic compounds profiles in milk fermented by lactic bacteria - Kondybayev, A.; Zhakupbekova, A.; Amutova, F.; Omarova, A.; Nurseitova, M.; Akhmetsadykova, Sh.; Akhmetsadykov, N.; Konuspayeva, G.; Faye, B. (International Journal of Biology and Chemistry, 2018)
The organoleptic properties of traditional dairy beverages done with non-conventional dairy species (horse, camel), popular in Central Asia, were rarely described in the literature. To characterize the Volatile Organic Compounds (VOC) profile of fermented mare milk, 12 samples of cow milk, used as matrix were inoculated by different strains from two types of bacteria (bacilli and cocci) isolated from natural fermented mare milk. The analysis performed by Gas Chromatography coupled with Solid-Phase Micro-Extraction allowed identification of 160 different compounds from the 12 strains, and 90 from natural fermented mare milk. After cluster analysis, 3 types of profiles were observed. Those profiles were distinct by the amount of acid compounds (low, medium, high), negatively related to aromatic and aliphatic hydrocarbons. The analysis of the mean volatile compound profile of each type of bacteria (bacilli and cocci) by factorial discriminant analysis showed that 3 molecules (oxime-methoxy-phenyl, propanedioic acid propyl and 2-propanamine) allowed to well class 100% of the samples. Further researches on bacterial identification and experiments with different fermentation matrices from other dairy species will be conducted.